(untitled) (Rudarsko-geološko-naftni zbornik, 2021)
Fluid front tracking is important in two-phase/component fluid flow in porous media with different heterogeneities, especially in the improved recovery of oil. Three different flow patterns of stable, viscous fingering, and capillary fingering exist based on the fluids’ viscosity and capillary number (CA). In addition, fluid front and sweep efficiency are affected by the heterogeneity of the porous medium. In the current study, the heterogeneous porous media are: (1) normal fault zone or cross-bedding with heterogeneity in permeability, and (2) a fracture or discontinuity between two porous media consisting of two homogeneous layers with very low and high permeabilities, in which immiscible water flooding is performed for sweep efficiency and streamlines tracking purposes. By considering the experimental glass micromodel and the simulation results of discontinuity, a crack is the main fluid flow path. After the breakthrough, fluid inclines to penetrate the fine and coarse grains around the crack. Moreover, an increase in flow rate from 1 and 200 (ml/h) in both the experimental and simulation models causes a reduction in the sweep efficiency from 14% to 7.3% and 15.6% to 10% by the moment of breakthrough, respectively. In the fault zone, the sweep efficiency and the streamline of the injected fluid showed a dependency on the interface incident angle, and the layers’ permeability. The presented glass micromodel and Lattice Boltzmann Method were consistent with fluid dynamics, and both of them were suitable for a precise evaluation of sweep efficiency and visualization of preferential pathway of fluid flow through cross-bedding and discontinuity for enhanced oil recovery purposes.